The Apostolic Fathers and the New Testament. By Clayton N. Jefford - Hall, Stuart George (The journal of theological studies, 2007)
Clayton N. Jefford has here produced a study bringing together the bodies of literature we call ‘New Testament’ and ‘Apostolic Fathers’. He took part in those Oxford seminars whose proceedings were reviewed in JTS, ns 57 (2006), pp. 695–700, but does not refer to their findings. He modestly aims to enlighten students already interested in the New Testament on the important neighbouring documents. It is good for its purpose, and the price is commendably modest. Jefford begins with a review of the dates and origins of the Apostolic Fathers so far as known; he is confessedly both conventional and corrigible.